Knowledge, attitudes and practices of cleaning staff regarding hepatitis B virus - Ahmadi, Z; Hosseni- Moghdam, M; Yaghmaei, F; Anisiyan, A (Advances in Nursing & Midwifery, 2007)
Abstract Background: Hepatitis B virus (HBV) is endemic in human population. It is estimated that 400 million people are infected with HBV in the world. Healthcare workers face with the risk of HBV infection during their work. Despite the increase of the disease, lack of knowledge regarding the mode of transmission and methods of prevention including immunization is still a threat. Purpose: The aim of this descriptive study was to assess knowledge, attitudes and practice of cleaning staff at Labafinejad Hospital regarding prevention of HBV. Methods: A questionnaire and a checklist of observation were used for data collection. The questionnaire consisted of 4 parts: 1) 18 questions regarding demographic characteristics; 2) 32 questions on knowledge, route of transmission and prevention of HBV infection; 3) 18 questions on attitude and 4) 4 questions regarding practice. It was validated and made reliable by content and test-retest methods (r=0.87). The questionnaire was distributed among 100 cleaning staff. Results: Finding showed that 75% of samples was male and 25% female. Knowledge score on universal precautions was moderate, attitude was good and practice was moderate. The results also showed that their attitude and practice were significantly correlated (P=0.009), practice had a significant correlation with age and sex (P=0.03). However, Furthermore, there was a significant correlation between knowledge with attitude, (P=0.35) and knowledge with practice (P=0.12). Conclusion: It can be concluded that cleaners had positive attitude toward HBV and implementation of universal precautions. On the other hand, cleaners had moderate knowledge and practice with regard to the mode of transmission. Therefore, performing comprehensive educational programs for cleaning staff regarding universal precautions seems necessary. Key words: HBV, Knowledge, Attitude, Practice.